Cyclotide structure-activity relationships: qualitative and quantitative approaches linking cytotoxic and anthelmintic activity to the clustering of physicochemical forces. - Sungkyu Park; Adam A Strömstedt; Ulf Göransson (PLoS ONE)
Cyclotides are a family of plant-derived proteins that are characterized by a cyclic backbone and a knotted disulfide topology. Their cyclic cystine knot (CCK) motif makes them exceptionally resistant to thermal, chemical, and enzymatic degradation. Cyclotides exert much of their biological activity via interactions with cell membranes. In this work, we qualitatively and quantitatively analyze the cytotoxic and anthelmintic membrane activities of cyclotides. The qualitative and quantitative models describe the potency of cyclotides using four simple physicochemical terms relevant to membrane contact. Specifically, surface areas of the cyclotides representing lipophilic and hydrogen bond donating properties were quantified and their distribution across the molecular surface was determined. The resulting quantitative structure-activity relation (QSAR) models suggest that the activity of the cyclotides is proportional to their lipophilic and positively charged surface areas, provided that the distribution of these surfaces is asymmetric. In addition, we qualitatively analyzed the physicochemical differences between the various cyclotide subfamilies and their effects on the cyclotides' orientation on the membrane and membrane activity.